2018
DOI: 10.1007/s13201-018-0706-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemistry, water quality and land use signatures in an ephemeral tidal river: implications in water management in the southwestern coastal region of Bangladesh

Abstract: Despite its complexity and importance in managing water resources in populous deltas, especially in tidal areas, literatures on tidal rivers and their land use linkage in connection to water quality and pollution are rare. Such information is of prior need for Integrated Water Resource Management in water scarce and climate change vulnerable regions, such as the southwestern coast of Bangladesh. Using water quality indices and multivariate analysis, we present here the land use signatures of a dying tidal rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Various studies such as National Research Council and Mono Basin Ecosystem Study Committee (1987), Council and Bennett (1993), Habersack and Nachtnebel (1995), Tenzer et al (1997), Hernandez and Ernest (1999), Schoonover et al (2005), Salvia-Castellví et al (2005, Salomons and Stigliani eds (2012), Mallick (2017), Thakur et al (2018), Denizman (2018), Jasrotia et al (2018), and Roy et al (2018) have shown that sediment-water interactions and the human activities such as agrarian and forestry practices, as well as the release of domestic wastewaters into the water bodies, are statistically related as have been analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies such as National Research Council and Mono Basin Ecosystem Study Committee (1987), Council and Bennett (1993), Habersack and Nachtnebel (1995), Tenzer et al (1997), Hernandez and Ernest (1999), Schoonover et al (2005), Salvia-Castellví et al (2005, Salomons and Stigliani eds (2012), Mallick (2017), Thakur et al (2018), Denizman (2018), Jasrotia et al (2018), and Roy et al (2018) have shown that sediment-water interactions and the human activities such as agrarian and forestry practices, as well as the release of domestic wastewaters into the water bodies, are statistically related as have been analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The region represents a low-lying coastal morphology that experiences frequent hydroclimatic hazards such as cyclones and storm surges, salinity invasions, and waterlogging [10]. The Rupsa-Bhairab-Pasur in the east and the Mayur river in the western boundary of the city play a key role in the agriculture-aquaculture farming systems of the area under investigation [48].…”
Section: Study Areamentioning
confidence: 99%
“…Bangladesh experiences a strong monsoonal climate, where biseasonal precipitation causes approximately 80% of yearly rainfall to occur between the months of June to September (e.g., [ 11 , 18 , 51 ]). This large seasonal difference in precipitation can lead to vast changes in surface water chemistry during different seasons, particularly in coastal regions (e.g., [ 2 , 59 , 63 ]).…”
Section: Methods and Study Areamentioning
confidence: 99%
“…Although there has been much research in Bangladesh on groundwater and contaminants such as arsenic (As) (e.g., [ 4 , 7 , 17 , 38 , 47 , 48 ]), less emphasis has been placed on surface water chemistry, especially in Southwest Bangladesh. Multiple studies in Bangladesh have geochemically examined tidally dominated rivers (hereafter called tidal channels) and adjacent waterways in both temporal and spatial ways (e.g., [ 2 , 3 , 24 , 33 , 59 , 63 ]). Studies have also looked at trace element concentrations in aquaculture ponds near the coastal region of Bangladesh [ 23 , 32 , 62 ] or in coastal Bangladesh rivers [ 36 , 52 ] and nonspecified lakes/ponds [ 1 ].…”
Section: Introductionmentioning
confidence: 99%